Problematika Pembelajaran Pendidikan Agama Islam di Kelas Vll SMP N 1 Tigo Nagari Kabupaten Pasaman - Ririn Juli Anggraini; Hidra Ariza; Liyarni Liyarni (Journal on Education, 2023)
Success in learning or in learning activities can be seen from changes in behavior in students, both input and output. Each subject has its own criteria and level of difficulty for educators and students, which are known as learning problems. Islamic religious education is a conscious effort (educator) to direct experience, knowledge, skills, and skills to the younger generation (students) so that one day they become Muslim human beings, fearing Allah SWT. Virtuous, complete personality who directly understands, lives and practices Islamic teachings in everyday life. The implementation of Islamic Education in our schools is still experiencing many problems which include educators, students, and learning media. The existence of problems in Islamic religious education raises less than optimal or has not fully achieved the goals of Islamic religious education in everyday life.